Implications for the Development of the National Capital of the Archipelago and Protection of Customary Law Communities: A Review of Law Number 3 of 2022 - Sari, Chika Fatika; Fadillah Zulfa Naftali (Arkus, 2024)
The construction of the National Capital City (IKN) of the Archipelago in East Kalimantan has significant implications for the customary law communities who inhabit the region. This research examines the implications of IKN development for the rights and lives of indigenous peoples based on Law Number 3 of 2022 concerning National Capital. This research uses qualitative methods with a normative juridical approach. Data was collected through document study and analysis of statutory regulations, especially Law No. 3 of 2022. The research results show that IKN development has potential positive and negative implications for customary law communities. On the one hand, IKN development can open up opportunities for access to education, health and the economy for indigenous communities. On the other hand, IKN development can also result in marginalization and deprivation of indigenous peoples' rights to customary lands and territories. Protection of the rights and lives of customary law communities in the development of IKN needs to be the government's main concern. Concrete efforts such as recognizing and establishing customary territories, involving indigenous communities in the development process, and providing fair access to resources need to be made to ensure equitable and sustainable IKN development.